Green Management of Universities in Thailand: Green Management of Universities in Thailand - Srionkong, Pallop; Yodsurang, Suphattra; Holumyong, Thitima (RATANABUTH JOURNAL, 2024)
A university is a place with a variety of areas of use, whether it is administrative, Education, Sports and Recreational Activities However, the management of the facility requires a budget and policies to manage the area and the public utility system well, otherwise the university will waste the budget. The integration of energy conservation and the environment has been incorporated into teaching, research, and university activities to create a working environment that is safe, environmentally friendly, and knows how to use energy efficiently and cost-effectively. Promote environmental protection This article presents ideas about operating a green university. This is one measure to support the implementation of the green university policy. which includes 1. The meaning of a green university 2. Importance of a green university 3. There are 6 criteria for ranking green universities. 4. Factors that can lead the university towards success in becoming a green university. It consists of 5 factors: 1) Setting environmental policy must be clear 2) Participation of personnel within the university 3) Setting target indicators, monitoring and evaluating 4) Integrating environmental activities/projects with operations according to the mission of the university 5) Development for Increase potential in environmental management.